Role of computed tomography angiography in the management of Zone II penetrating neck trauma in patients with clinical hard signs. Issue 6 (December 2015) - Schroll, Rebecca; Fontenot, Tatyana; Lipcsey, Megan; Heaney, Jiselle Bock; Marr, Alan; Meade, Peter; McSwain, Norman; Duchesne, Juan
Abstract : BACKGROUND: The Western Trauma Association (WTA) describes the management of Zone 2 penetrating neck trauma (PNT) and recommends neck exploration (NE) for patients with clinical hard signs (HS). We hypothesize that in stable patients with HS, the management of PNT augmented by computed tomography angiography (CTA) results in fewer negative NE results. METHODS: This was a 4-year retrospective review of adult patients with Zone 2 PNT at a Level I trauma center. Stable patients with WTA-defined HS (airway compromise, massive subcutaneous emphysema/air bubbling through wound, expanding/pulsatile hematoma, active bleeding, shock, focal neurologic deficit, and hematemesis) who underwent CTA instead of emergent exploration were identified. Sensitivity, specificity, positive predictive value, and negative predictive value for CTA were calculated. A comparison was made between the rates of negative NE results in patients with HS who received a CTA versus the rate that would have occurred in the same patients if the WTA algorithm had been followed. Missed injury rates were also compared. RESULTS: Of 183 PNT patients, 23 had HS and underwent CTA. Of the 23, 5 had a positive CTA findings and underwent NE, while 17 had a negative CTA findings and did not require NE. There was one false-negative in a patient who developed an expanding hematoma following negative neck CTA finding. Sensitivity, specificity, positive predictive value, and negative predictive value for CTA in the presence of HS were found to be 83%, 100%, 100%, and 94%, respectively. The addition of CTA to the WTA algorithm for this patient group significantly decreased the rate of negative NE (0 of 23 vs. 18 of 23, p < 0.001) without a significant increase in the rate of missed injury (1 of 23 vs. 0 of 23, p = 0.323). The use of CTA prevented 17 unnecessary NEs. CONCLUSION: CTA addition to the management of hemodynamically stable patients with HS in PNT significantly decreased the rate of negative NE result without increasing missed injury rate. Prospective study of CTA addition to the WTA algorithm is needed. LEVEL OF EVIDENCE: Care management/therapeutic study, level IV.